PENERAPAN DIVERSI SEBAGAI UPAYA PERLINDUNGAN TINDAK PIDANA ANAK DI KOTA SAMARINDA BERDASARKAN UUD NO. 11 TAHUN 2012 - Muhammad Alfian Nur (Universitas 17 Agustus 1945 Samarinda, 2017)
ABSTRACT Diversi is an act or action to divert or place the offender of a crime of a child out of the criminal justice system. The diversion process is based on the fact that the criminal justice process of child offenders through the criminal justice system poses more harm to the growth conditions, the physical and mental development of the child than the good so it is better to avoid it out of the criminal justice system.The approach method used in this research is empirical juridical method, empirical juridical method. empirical juridical method, or legal procedure occurring within the community. Empirical juridical research is a field study that is the study that examines the rules of law which are then combined with data and behavior that live in the midst of society. Data / subject matter in this research is through Sat Reskrim Polresta Samarinda Unit PPA, Samarinda State Attorney, State Court of Samarinda. Keywords: Criminal, Protection, Child, Diversi